Comparative genomic analyses reveal genetic characteristics and pathogenic factors of Bacillus pumilus HM-7 - Wang, Qian; Zhang, Lei; Zhang, Yiju; Chen, Huamin; Song, Jianghua; Lyu, Mingjie; Chen, Rui; Zhang, Lixin (Frontiers in Microbiology, 2022)
Bacillus pumilus plays an important role in industrial application and biocontrol activities, as well as causing humans and plants disease, leading to economic losses and biosafety concerns. However, until now, the pathogenesis and underlying mechanisms of B. pumilus strains remain unclear. In our previous study, one representative isolate of B. pumilus named HM-7 has been recovered and proved to be the causal agent of fruit rot on muskmelon (Cucumis melo). Herein, we present a complete and annotated genome sequence of HM-7 that contains 4,111 coding genes in a single 3,951,520 bp chromosome with 41.04% GC content. A total of 3,481 genes were functionally annotated with the GO, COG, and KEGG databases. Pan-core genome analysis of HM-7 and 20 representative B. pumilus strains, as well as six closely related Bacillus species, discovered 740 core genes and 15,205 genes in the pan-genome of 21 B. pumilus strains, in which 500 specific-genes were identified in HM-7 genome. The average nucleotide identity (ANI), and whole-genome-based phylogenetic analysis revealed that HM-7 is most closely related to the C4, GR8, MTCC-B6033, TUAT1 and SH-B11 strains, but evolutionarily distinct from other strains in B. pumilus. Collinearity analysis of the six similar B. pumilus strains showed high levels of synteny but also several divergent regions for each strains. In the HM-7 genome, we identified 484 genes in the carbohydrate-active enzymes (CAZyme) class, 650 genes encoding virulence factors, and 1,115 genes associated with pathogen-host interactions. Moreover, three HM-7-specific regions were determined, which contained 424 protein-coding genes. Further investigation of these genes showed that 19 pathogenesis-related genes were mainly associated with flagella formation and secretion of toxic products, which might be involved in the virulence of strain HM-7. Our results provided detailed genomic and taxonomic information for the HM-7 strain, and discovered its potential pathogenicity mechanism, which lay a foundation for developing effective prevention and control strategies against this pathogen in the future.